Model Pencatatan Intellectual Capital dalam Menghadapi Perubahan Paradigma Akuntansi Baru - Hendarti, Henny (Journal the Winners: Economics, Business, Management, and Information System Journal, 2007)
The more competitive of competition in business world has made the company having competitive advantage continuously through the management of human resource. Competitive advantage can be created with intellectual capital, by human capital, structural capital, customer capital, commitment, and competence. The article discuss intellectual capital record model in facing the changes of new accounting paradigm.